2011
DOI: 10.4102/hts.v67i2.899
|View full text |Cite
|
Sign up to set email alerts
|

Cohabitation and premarital sex amongst Christian youth in South Africa today: A missional reflection

Abstract: This article explored the rising trends of cohabitation and premarital sex amongst Christian and non-Christian youth in South Africa that is becoming more socially acceptable. Moving from a premise of engaging in these practices, which is not biblically justified, to what a missional Christian church can do, this article sought to bring the numbers of those who cohabit and engage in premarital sex down. The thesis of this article was that a missional church should view cohabitation and premarital sex as fronti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…Although the number of married/cohabiting students is small in the study population, the practice of cohabitation is increasingly becoming common among South Africa's more highly educated (Mashau 2011). Our findings are in concert with earlier studies (Chandran et al 2012;Hargreaves et al 2009) which reported that married/cohabiting students were significantly more likely to use condoms consistently than unemployed women in the general population.…”
Section: Discussionsupporting
confidence: 84%
“…Although the number of married/cohabiting students is small in the study population, the practice of cohabitation is increasingly becoming common among South Africa's more highly educated (Mashau 2011). Our findings are in concert with earlier studies (Chandran et al 2012;Hargreaves et al 2009) which reported that married/cohabiting students were significantly more likely to use condoms consistently than unemployed women in the general population.…”
Section: Discussionsupporting
confidence: 84%
“…The reason is that "it is only after Adam and Eve were joined together in marriage and the Lord had blessed them that he gave them the go-ahead to have sex and multiply." 25 For Keller, sex is sacred and it is "very good (Gen. 1:31). God would not create and command something to be done in marriage (1 Cor.…”
Section: The Bible and Premarital Sexmentioning
confidence: 99%
“…26 Biblically, God designed a "heterosexual monogamous relationship, wherein sex is to be enjoyed within the marriage context." 27 God's design for sex was for it to be expressed by and between a man and a woman, who are joined together as couples because of love. "Those who exchange their vows, 'until death do us part', are also given the license to share a blanket together."…”
Section: The Bible and Premarital Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the concept of family has changed from the large multiple-parents extended families to the small two-parent nuclear families; and nowadays to even smaller single-parent families. Researchers (e.g., Ellwood and Jencks, 2004;Mashau, 2011) have argued that explaining the spread of single-parent and cohabiting-parent families has been both an intellectual challenge and a source of persistent frustration for social scientists. The increasing diversity of family structure in African countries compels need for the contributions of globalisation processes to the public permissiveness and growing popularity of single-parent and cohabiting-parent families in Africa to be examined in this paper, including the prevalence of these structures as measured by Demographic and Health Surveys (DHS).…”
Section: Statement Of the Problemmentioning
confidence: 99%